LISTA DE BRUCHIDAE DEL ESTADO DE QUERÉTARO, MÉXICO (INSECTA: COLEOPTERA) - Luna Cozar, Jesús; Romero Nápoles, Jesús; W. Jones, Robert (Instituto de Ecología, A.C., 2002)
A checklist of the family Bruchidae (Coleoptera) from Querétaro is presented. A total of 57 species and 14 genera, a new genus and new species are recorded. The fauna of Bruchidae recorded from Querétaro represents 17.6% of the species and 66% of the genera known from Mexico. The genera Acanthoscelides, Stator y Mimosestes had the greatest number of species recorded. The Bruchidae from the state had geographic distributions in three basic groups of similar proportions: 1) Mexico and North America (28%), 2) Mexico or México and Central America (38%) and 3) of wide spread distribution (37%).